Forced Return Flow Deep in the Subduction Channel, Syros, Greece. Issue 1 (20th January 2020) - Ring, Uwe; Pantazides, Hermes; Glodny, Johannes; Skelton, Alasdair
Abstract: We present the results of a detailed structural study in the Cycladic Blueschist Unit at Fabrika on Syros Island, Greece, and discuss their significance for tectonic processes at the subduction interface. Some samples record top‐to‐the‐west shear reflecting prograde (burial), peak high‐pressure (HP) and initial decompression (exhumation) conditions. Other nearby samples record top‐to‐the‐east shear during HP metamorphism and exhumation. Some rocks re‐equilibrated at greenschist‐facies conditions and record top‐to‐the‐west shear. Greenschist‐facies top‐to‐the‐west shear is also found at the base of non‐HP upper units above the Fabrika HP sequence. We interpret the HP structures to reflect forced return flow and incipient formation of an extrusion wedge in the subduction channel. The HP top‐to‐the‐west structures resulted from thrusting along the base of the wedge and started to form during burial before the rocks reached their deepest point. The HP top‐to‐the‐east structures reflect deformation near the top of the developing extrusion wedge. After considerable exhumation during ongoing subduction, out‐of‐sequence, top‐to‐the‐west thrusts emplaced the non‐HP upper units above the exhuming extrusion wedge ~10 Myr after the wedge initially formed. Our work suggests that the HP rocks were considerably exhumed during sustained lithospheric shortening in the subduction channel by forced return flow. Because return flow is controlled by the velocity of the subducting slab, it may explain why HP rocks can be exhumed at subduction rates. On the regional scale we find that four distinct HP belts were sequentially accreted and exhumed between ~50 and 20 Ma suggesting continuous subduction‐channel return flow in the Hellenic subduction zone. Key Points: Structures are interpreted to reflect forced return flow in subduction channel Structures in high‐pressure and greenschist‐facies rocks indicate sustained lithospheric shortening New and novel interpretation of subduction‐related structures in Cycladic Blueschist Unit